PENGARUH KEEFEKTIFAN SISTEM PENGENDALIAN INTERNAL, KETAATAN AKUNTANSI, ASIMTERI INFORMASI DAN MORALITAS INDIVIDU TERHADAP KECENDRUNGAN KECURANGAN AKUNTANSI DENGAN PERILAKU TIDAK ETIS SEBAGAI VARIABEL INTERVENING (Studi Empiris Pada Satuan Kerja Perangkat - Yulita Fitri; Nurazlina '; Al Azhar A ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This research are to analyze effectiveness of internal control, compliance to accounting rules, information asymmetry and individual morality affect the accounting fraud tendencies by the unethical behavioras an intervening variable. This research was conducted at SKPD Riau Province. The sample was 89 employee level officials Echelon III and Echelon IV. Methods of data collectionin this study with a survey method with questionnaire instrument. Data analysis method used totest the quality of data which include validity, reliability, and test hypothes is is path analysis, test Sobel and boostrapping using software SmartPLS. Hypothesis testing using partial least square test showed that the variable information asymmetry and individual morality significantly influence the accounting fraud tendencies by the unethical behavioras an intervening variable. While the variable effectiveness of internal control and compliance to accounting rules does not affect accounting fraud tendencies by the unethical behavioras an intervening variable. Value of R-Square indicates that the variables jointly effectiveness of internal control, compliance to accounting rules, information asymmetry, individual morality and the unethical behavior contribute to the dependent variable (affect the accounting fraud tendencies) of 95.80%, while the remaining 4.20% is explained by other variables outside the research model.Keywords : Effectiveness of Internal Control, Compliance to Accounting Rules, Information Asymmetry, Individual Morality, and Accounting Fraud Tendencies Unethical Behavior